Quantifying aboveground biomass and carbon stock of Acacia mangium at Bandar Jeli, Jeli, Kelantan - Siti Mariam Hamid@Awang (2024)
Acacia mangium is a fast-growing tropical tree species that is commonly used in reforestation and agroforestry projects due to its adaptability and rapid growth. In Malaysia, particularly in Jeli, Kelantan, there is limited data on above ground biomass and carbon storage potential of Acacia mangium. Measuring this parameter would provide valuable information for forest management and carbon accounting. Moreover, there is uncertainty in using standard allometric models to estimate biomass and carbon stocks in Acacia mangium. This study aims to estimate the biomass of Acacia mangium above ground in a representative stand in Bandar Jeli, Jeli, Kelantan, and to evaluate the carbon storage of above ground biomass. The diameter at breast height (DBH) is measured using a diameter tape. Aboveground biomass (AGB) was calculated using a specific allometric equation that required only DBH data, and carbon stocks were estimated using guidelines from the Intergovernmental Panel on Climate Change (IPCC). The results showed that the mean value of diameter at breast (DBH) was 14.79 cm while total of 45.44 AGB was 11.36 Mg/ha, and carbon stock was 21.36 MgC/ha between plots. This study succeeded in generating carbon stock data of Acacia mangium in Bandar Jeli using AGB. This data can contribute to the estimation of carbon sequestration and improve the understanding of carbon dynamics in the region.